Paradigma fikih baru Jamal al-Banna dan relevansinya terhadap pembaruan peran perempuan dalam hukum keluarga Islam (Fiqh al-Munakahat) - Syaiful Bahri (State Institute of Islamic Studies (IAIN) Salatiga, 2019)
The role of women, according to classical fiqh (Islamic law) literature, especially fiqh al-Munakahat (Islamic family law), tends to be regarded as a complementary part of domestic life. Their role is limited to the domestic territory, and restrain to play a public role. This paper tries to reconstruct the role of women in Islamic family law, utilizing the new fiqh paradigm initiated by Jamal al-Banna. To answer this problem, the author conducted a literature study by examining two works of Jamal: Nahwa Fiqhin Jadid and Al-Mar'ah al-Muslimah bayna Tahrir Al-Qur'an wa Taqyid al-Fuqaha'. This paper concludes that some issues regarding the role of women in Islamic family law need renewal. There are four crucial issues that are reviewed using the new fiqh paradigm of Jamal al-Banna, namely the minimum age of marriage, wali’s ijbar rights, polygamy, and divorce.